Analysis Of The Influence Of Safety Climate On Occupational Safety Behavior In The Industry: Literature Review - Adela Virzadiatma (CV. AFDIFAL MAJU BERKAH, 2026)
Occupational Health and Safety (OHS) is a crucial component of industrial management systems aimed at reducing workplace accidents, injuries, and losses arising from occupational risks. One of the factors influencing safety performance is safety climate, defined as employees’ perceptions of the extent to which the organization prioritizes and implements safety practices. This study aims to analyze the effect of safety climate on safety behavior in industrial settings. The method used was a literature review, limited to publications from the last five years in both Indonesian and English, particularly focusing on high-risk industries. The review of five selected journals indicates that safety climate has a positive and significant influence on safety behavior at work. The main factors shaping safety climate perceptions include management commitment, safety communication, OHS training, and safety leadership. Furthermore, safety climate acts as a mediating variable linking safety leadership and safety knowledge to safe work behavior. In conclusion, the stronger employees’ perceptions of safety climate, the higher their level of compliance and participation in workplace safety practices within industrial environments.